2017
DOI: 10.1111/1750-3841.13838
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Mushrooms to Reduce Overall Sodium in Taco Filling Using Physical and Sensory Evaluation

Abstract: Although diet can significantly reduce the risk of heart disease, American consumers continue to eat detrimental diets high in fat and sodium. Products need to be made that decrease fat and sodium intake while still delivering acceptable taste. Mushroom substitution into meat-based products can be a strategy to develop products that can decrease fat and sodium consumption while increasing vegetable intake without compromising the quality and taste consumers demand. This research shows how consumers can accept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…It implied that the sensory properties of formulated patties were quite acceptable. Studies have shown consumer acceptance toward meat products substituted with mushroom: The overall liking of variant beef patties with mushroom substitution up to 30% was similar to the all‐meat control (Wong et al., 2019); variant dishes with mushroom up to 45% had similar overall liking to the all‐meat control (Wong et al., 2017, 2019); and no significant difference in overall liking was observed among six recipes where beef had been partially substituted with mushrooms (Guinard et al., 2016). It is well known that mushrooms have certain “meaty” taste and are suitable to be used as meat analogues (Kumar et al., 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It implied that the sensory properties of formulated patties were quite acceptable. Studies have shown consumer acceptance toward meat products substituted with mushroom: The overall liking of variant beef patties with mushroom substitution up to 30% was similar to the all‐meat control (Wong et al., 2019); variant dishes with mushroom up to 45% had similar overall liking to the all‐meat control (Wong et al., 2017, 2019); and no significant difference in overall liking was observed among six recipes where beef had been partially substituted with mushrooms (Guinard et al., 2016). It is well known that mushrooms have certain “meaty” taste and are suitable to be used as meat analogues (Kumar et al., 2017).…”
Section: Discussionmentioning
confidence: 98%
“…The focus of such research has been consumer acceptance of different dishes or patties with mushrooms added. For example, consumer tests involving the addition of mushroom to savory products such as sausage‐type, beef patties, or chicken patties (Akesowan, 2016; Guinard et al., 2016; Spencer & Guinard, 2018; Stephan et al., 2018; Tom et al., 2018; Wong et al., 2017, 2019). Additionally, several studies have evaluated different mushroom powders applied to bakery products and their consumer acceptance (Salehi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the results from this work displayed statistical differences with color being less liked when the mushroom usage level as at 10% and 20% indicating that the mushroom type, in this case white mushrooms, may influence the consumer acceptance. Unformed beef applications, such as taco-based fillings, have also shown acceptable sensory quality attributes using white button mushrooms up to levels as high as 45% (Wong et al, 2017).…”
Section: Hedonic Sensory Study Optimizing Meat Extender Concentrationmentioning
confidence: 99%
“…Error bars presented are the calculated standard deviations within each treatment. Data points with an *indicate a significant difference from the control (Dunnett, p = 0.05)Wong et al (2017) also identified mechanical differences in meatbased products, specifically taco filling substituted with mushrooms.Apparent stress at 50% deformation significantly decreased at 50% substitution, while the residual apparent stress decreased at lower substitution levels, for example, 25%. WanRosli et al (2011) reported lower values of selected textural characteristics for chicken patties substituted with 25% and 50% blanched oyster mushroom.…”
mentioning
confidence: 92%
“…Twenty mushrooms were used and Texture Test (TPA) was performed on mushroom cap using Instron (STM-Santam20, Iran) under the conditions as follow: test speed of 2 mm/s, pretest speed of 10 mm/s, and 30% strain. Then, force-time diagram was calculated using the software installed on the apparatus and the firmness and elasticity of the mushroom samples were calculated using the software (Wong et al, 2017). Both sterile nutrients agar were kept until reaching the desired number for performing microbial tests for 24 hr at 37 8C.…”
Section: Texture Analysis Of the Samplesmentioning
confidence: 99%